Volume 13: New Developments in Simulation Methods and Software for Engineering Applications; Safety Engineering, Risk Analysis 2009
DOI: 10.1115/imece2009-10277
|View full text |Cite
|
Sign up to set email alerts
|

On the Construction and Use of Surrogate Models for the Dynamic Analysis of Multibody Systems

Abstract: This study outlines an approach for speeding up the simulation of the dynamic response of vehicle models that include hysteretic nonlinear tire components. The method proposed replaces the hysteretic nonlinear tire model with a surrogate model that emulates the dynamic response of the actual tire.The approach is demonstrated via a dynamic simulation of a quarter vehicle model. In the proposed methodology, training information generated with a reduced number of harmonic excitations is used to construct the tire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Ardeh et al [37] and Han et al [40] have reported that their surrogates trained on synthetic data offered high accuracy and efficiency compared to the full, nonlinear simulation models. Ardeh et al [37] have built a surrogate of a tire using a feed-forward neural network. The surrogate model was designed Table 1 Summary of papers on data-driven modeling of multibody systems using deep learning.…”
Section: Surrogate Subsystem Models In the Multibody Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ardeh et al [37] and Han et al [40] have reported that their surrogates trained on synthetic data offered high accuracy and efficiency compared to the full, nonlinear simulation models. Ardeh et al [37] have built a surrogate of a tire using a feed-forward neural network. The surrogate model was designed Table 1 Summary of papers on data-driven modeling of multibody systems using deep learning.…”
Section: Surrogate Subsystem Models In the Multibody Frameworkmentioning
confidence: 99%
“…Topic DL Methods SD MD SM Surrogate models Ardeh et al [37] Submodel of a tire FFNN Azzam et al [38] Virtual sensor for loads on wind turbine gearbox FFNN García Peyrano et al [39] Mechanical unbalance of the flexible rotor of a steam turbine FFNN, SVM Inverse dynamics of robotic manipulators SOUL, RNN Rane et al [46] Internal forces in musculoskeletal models during motion CNN, FFNN Ren and Ben-Tzvi [36] Inverse kinematics and dynamics of robotic manipulators GAN Nasr et al [47] Inverse muscle dynamics in musculoskeletal models…”
Section: Papermentioning
confidence: 99%